Propuesta de Mejora bajo el concepto de Lean Manufacturing para la línea De producción Soldadura de la empresa Pavco Wavin (2023)
This project consists of carrying out a study of the current situation of the plant through a diagnosis to later analyze, plan and implement a proposal for improvement in Lean Manufacturing tools in a company plant dedicated to the manufacture of liquid welding that is a solution of PVC or CPVC resin, specially formulated to make the joints between pipes and polyvinyl chloride accessories. The proposal will be diagnosed, evaluated and coasted based on Lean Manufacturing tools, special emphasis will be placed on SMED, continuous improvement Kaizen, Poka-Yokeproof yoke, standardization, TPM, 5S's with the aim of increasing productivity, improving quality and eliminating everything that does not add any value to the product.